"Coming Out" to Parents in a Christian Context: A Consensual Qualitative Analysis of LGB Student Experiences. Issue 1 (8th April 2020) - Reed, Jeffrey L.; Stratton, Stephen P.; Koprowski, Gregory; Dillon, Christina; Dean, Janet B.; Yarhouse, Mark A.; Lastoria, Michael; Bucher, Emma K.
Abstract : Disclosures of same‐sex attraction are some of the most difficult experiences for lesbian, gay, and bisexual (LGB) individuals. For LGB individuals of faith, disclosure to parents is often complicated by the intersection of religion/spirituality and sexuality. This study presents a grounded theory about a particular subgroup to address gaps in the literature concerning how LGB students on Christian college campuses describe and experience their parental disclosures. Consensual qualitative research analysis (Hill, Knox, Thompson, Williams, & Hess, 2005; Hill, Thompson, & Williams, 1997) revealed themes related to predisclosure influencing factors, the disclosure event experience, and longer term impacts of the disclosure. Implications for parents, counselors, and college faculty/staff are provided.